8th International Congress on Science and Skiing, March 11-15, 2019, Vuokatti, Finland. Book of Abstracts (University of Jyväskylä; Vuokatti Sports Technology Unit of the Faculty of Sport and Health Sciences of the University of Jyväskylä, 2020)
The Vuokatti Sports Technology Unit of the University of Jyväskylä is proud to present the Abstract Book of the 8th International Congress on Science and Skiing (ICSS 2019), held in Vuokatti, Finland, March 11-15, 2019. The scientific programme offers a broad interdisciplinary spectrum of current research in Nordic and Alpine skiing. The Abstract Book includes altogether 61 oral presentations of which five are keynotes, 13 are invited and 10 are in the Young Investigator Award Competition. In addition there are 20 poster presentations. The entire scope of relevant topics in skiing will be covered by these presentations. The highlights of the congress will be the five keynotes, presented by Erich Müller (Austria), David Bacharach (USA), Øyvind Sandbakk (Norway), Maarit Valtonen (Finland), and Walter Herzog (Canada). In order to maintain a high scientific standard required of this congress, a peer review process was utilized in the selection of the papers. Each abstract was sent to at least one member of the scientific committee to be reviewed. The papers were examined regarding content, topics and structure according to the guidelines of ICSS. Most of the abstracts were accepted, some of them after minor improvements. We want to thank the members of the scientific committee for the work they did reviewing the abstracts. In addition to the Abstract Book the Proceedings will be published by Meyer & Meyer in 2020.